Cyber-Risk Management Menggunakan NIST Cyber Security Framework (CSF) dan Cobit 2019 pada Instansi XYZ - Julianto, Andhika Sigit; Hikmah, Ira Rosianal; Yasa, Ray Novita (Info Kripto, 2024)
Current technological developments trigger companies or organizations to use Information Technology (IT) as a service base and optimize business processes. IT can provide opportunities in the government sector to develop state apparatus through implementing the Electronic-Based Government System (SPBE). Central and Local Government Agencies have implemented SPBE and contributed to the efficiency and effectiveness of government administration. Ensuring the sustainability of SPBE and reducing the impact of risk is the goal of risk management, with a process of identification, analysis, control, monitoring, and evaluation of risks based on risk management determined by the government. XYZ Agency is an agency that operates in the fields of communication and information, coding and statistics. XYZ Agency also implemented an Electronic Based Government System (SPBE). In this study, Cyber-risk management was designed using NIST CSF and COBIT 2019. In designing cyber-risk management, using 6 stages, namely Prioritized and Scope, Orient, Create a Current Profile, Conduct Risk Assessment, Create a Target Profile, and Determine, Analyze, and Prioritize Gaps. In this study, there are 28 assets, 17 threats, 13 vulnerabilities, and 12 controls implemented. With these results obtained 111 risks, there are 35 risks in the high category, 63 risks in the medium category, and 13 risks in the low category. The final result of this research is the preparation preparation of a cyber-risk management design by grouping the recommended actions based on Work Products (WP) and Generic Work Products (GWP) which become a work program for XYZ Agency.